Abiotic factors and the growth of cyanobacteria in surface water reservoirs in the state of Pernambuco - Regis, Andreia Souza; da Silva, Ronaldo Faustino; de Oliveira, Fabio Henrique Portella Corrêa; de Oliveira, Eduardo José Alécio (Seven Editora, 2024)
Objective: Analyze the relationship between physical-chemical and climatic abiotic factors in relation to the occurrence of cyanobacteria genera in surface water reservoirs used for public supply in the state of Pernambuco. Literature Review: Information is presented on cyanobacteria and the consequences of the release of untreated effluents on the eutrophication of surface waters with effects on the growih of cyanobacteria and consequences for aquatic organisms and humans and the climate in regions of Pernambuco where water reservoirs are located, Method: Quali-quantitative descriptive and exploratory approach to the analysis of abiotic variables (pH, CE., Turbidity, Color, Calcium, Magnesium, Chlorides, Sulfate, Nitrogen, Phosphate, Alkalinity, Hardness, Iron, Manganese, Aluminum and rainfall) and biotic (Cyanobacteria density), collected from the Pernambuco Sanitation Company — COMPESA. The samples were from eutrophic freshwater reservoirs in Pernambuco collected between 2010 and 2020. Results and Discussion: The most frequent genus of cyanobacteria was Raphidiopsis/Cylindrospermopsis, found abundantly in all reservoirs, where the increase in color, turbidity and pH were positively correlated with the presence of Microcystis and Raphidiopsis/Cylindrospermopsis, and negatively with the increase in toughness. A positive correlation was also observed between hardness and the increase in Planktorhrix density. Research Implications: Generate guidelines for drinking water supply presenting tools for understanding abiotic conditions that influence the growth of cyanobacteria, in order to outline control or services, ‘mitigation strategies in ETAs. Originality/Value: Generate useful information in the evaluation of abiotic parameters and cyanobacteria density, observed over a long period (10 years), showing positive/negative correlations in surface waters used for human consumption. DOI:https://doi.org/10.56238/sevened2024.026-040